Coping with School Violence Behavior of High School Students (Research on High School Students in Da Nang City) - Yen, Tran Thanh; Nguyen, Phung Huu; Tram, Vo Thi (RA Journal of Applied Research, 2021)
In today’s society, there are still school violence behaviors that affect simultaneously seriously to the physical and mental health of students as well as their academic performances. This article will present how high school students in the city of Da Nang cope with these related problems. A study with the participation of 423 students at seven schools in Da Nang city was carried out to describe the fact how students cope with school violence behaviours. Its result shows that the main cause of school violence behavior comes from students’ witnessing various types of violence. In addition, students apply positive responses through actions and emotions when faced with school violence behaviors. Based on the result obtained, the study recommends measures to partially affect the way the schools and families develop their solutions, as well as directly affect the survey subjects.